(untitled) (Ameghiniana, 2016)
This paper reports on the biostratigraphic, paleobiogeographic and paleoecologic aspects of palynoflora recovered from sedimentary rocks preliminarily assigned to the Lago Colhué Huapi Formation, in the Golfo San Jorge Basin. The present palynological assemblage includes Maastrichtian marker species of the austral Proteacidites/Nothofagidites Province such as Quadraplanus brossus and Tubulifloridites lilliei. Typical species of the Maastrichtian paleotropical Palmae Province, Buttinia andreevi and Gabonisporis vigourouxii, are also recognized in the palynoflora. These facts indicate the mixed character of the paleoflora and the prevalence of transitional climatic conditions at the paleolatitude of the Chubut Province in the uppermost Cretaceous. The palynoflora composition suggests the local existence of a warm and low energy freshwater body. Resumen. PRIMER REPORTE DE UNA PALINOFLORA MAASTRICHTIANA EN LA CUENCA DEL GOLFO SAN JORGE, PATAGONIA CENTRAL, ARGENTINA. Este artículo informa sobre los aspectos bioestratigráficos, paleobiogeográficos y paleoecológicos de una palinoflora recuperada de rocas sedimentarias asignadas de forma preliminar a la Formación Lago Colhué Huapi, en la Cuenca del Golfo San Jorge. La asociación palinológica incluye especies marcadoras del Maastrichtiano de la Provincia austral Proteacidites/Nothofagidites, como Quadraplanus brossus y Tubulifloridites lilliei. También se reconocen en la palinoflora especies típicas del Maastrichtiano de la Provincia paleotropical Palmae como Buttinia andreevi y Gabonisporis vigourouxii. Estos hechos indican el carácter mixto de la paleoflora y la prevalencia de condiciones climáticas transicionales en la paleolatitud de la Provincia de Chubut. La composición de la palinoflora sugiere la presencia local de un cuerpo de agua dulce templada y de baja energía.